An usborne flap book: see inside science - Frith, Alex; King, Colin (Usborne Publishing Heshan, 2006)
Journey into the mysteries of outer space. Meet the creatures that swing through rainforest jungles. Explore the hidden world inside an atom. This volume is packed with illustrations and flaps that bring alive the world of science